Behiştî of Vize and The Shahrangiz of Bursa - Fatih Tığlı (İstanbul Üniversitesi Edebiyat Fakültesi Türk Dili ve Edebiyatı Dergisi)
Behiştî of Vize was a sixteenth-century poet who wrote in the shahrangiz genre, which featured well-known, prominent, or famous people and beauties in the context of a particular city in classical Turkish literature. The shahrangiz of Behiştî, known by the pseudonyms Vizeli, Vaiz, and Sânî, to avoid confusion with other poets bearing the same pseudonym, intertwines with the shahrangiz of the Mesîhî and the Kerîmî. It is part of a poem collection manuscript with scattered pages, registered as Mil Yz A 827 in Ankara National Library catalog. According to historical records, Behiştî was born in Vize, studied in Istanbul, was assigned to Çorlu, and later went to Bursa, as perceived by the statements in his shahrangiz. Shahrangiz, believed to be missing a section at the beginning, consists of a total of 113 couplets, including a 108-couplet mathnawi and a 5-couplet ghazal at the end. This text is written with an aruz meter generally preferred for the shahrangiz, the hezec: mefâîlün/mefâîlün/feûlün.